1991
DOI: 10.1002/ar.1092290306
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of cathepsin D in rat ventral prostate: Evidence for castration‐induced expression of cathepsin D in basal cells

Abstract: Cathepsin D (EC3.4.23.5) is an aspartyl endopeptidase involved in lysosomal proteolysis. Its functional role is uncertain. This study was undertaken to determine the cellular and subcellular distribution of cathepsin D in the normal rat ventral prostate and its possible role in the castration-induced atrophy of the gland. Cathepsin D was localized immunohistochemically to perinuclear lysosomes in secretory cells, in capillary endothelial cells, and, occasionally, in stromal cells of the untreated animal. Castr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0
3

Year Published

1993
1993
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 54 publications
4
15
0
3
Order By: Relevance
“…SGP-2 staining became associated with large rounded vacuoles. Morphologically, these SGP-2-positive, intracellular vacuoles fit the typical description of autophagic vacuoles and/or secondary lysosomes seen to form in other tissues undergoing castration-induced regression [30,31]. Increased autophagic and heterophagic vacuole formation by caput principal cells in response to orchiectomy has been reported, supporting our concept that the SGP-2-positive vacuoles could represent autophagic vacuoles and/or secondary lysosomes [29].…”
Section: Discussionsupporting
confidence: 65%
“…SGP-2 staining became associated with large rounded vacuoles. Morphologically, these SGP-2-positive, intracellular vacuoles fit the typical description of autophagic vacuoles and/or secondary lysosomes seen to form in other tissues undergoing castration-induced regression [30,31]. Increased autophagic and heterophagic vacuole formation by caput principal cells in response to orchiectomy has been reported, supporting our concept that the SGP-2-positive vacuoles could represent autophagic vacuoles and/or secondary lysosomes [29].…”
Section: Discussionsupporting
confidence: 65%
“…This suggestion was consistent with previous observations that expression of other members of the cathepsin family of enzymes are up-regulated during apoptosis and that loss of spermatogenic cells is due to apoptotic cell death [5,[15][16][17][18][19][20]. To determine whether germ cells in regressing tubules of 23-mo-old rats were dying by apoptosis, we used an in situ method to identify apoptotic cells in serial sections of the testes that had been used to analyze CP-2/cathepsin L mRNA expression in normal, regressing, and regressed tubules.…”
Section: Identification Of Apoptotic Germ Cells In Regressing Seminifsupporting
confidence: 90%
“…Increased autophagosomes have been observed in the epithelial cells of the rat prostate gland after castration. 11,12 However, the specific relationship between autophagy and androgen is poorly known. In the study, we used LNCaP cells as an androgen-dependent prostate cancer cells model.…”
Section: Discussionmentioning
confidence: 99%
“…10 Previous studies have also reported that the number of autophagosomes was increased in the epithelial cells of rat prostate gland after castration. 11,12 Thus, it is probable that autophagy plays a role in prostate cancer cells when there is a lack of androgen.…”
Section: Introductionmentioning
confidence: 99%